Analisis Kesalahan Berbahasa Dalam Bahasa Arab - Nurkholis Nurkholis (Institut Agama Islam Negeri Metro, 2018)
In language activities often have errors, this is due to some problems that exist in the first and second language. Some student do not realize that the language used still has many errors. These errors are not only physical, but also a sign of imperfect knowledge and mastery of the code. The student has not yet internalized the (second) language rules they are learning. With held error analysis is expected the language learners at any level can minimize errors in his language. Analysis of language errors is a process based on analyzing the error of a learned person with an object (language) that has been targeted. The targeted language can be either the mother tongue or the target language